2005
DOI: 10.1007/s10566-005-7755-7
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Resilience Among Children in Child Welfare, Corrections, Mental Health and Educational Settings: Navigation and Negotiation

Abstract: In this paper I explore how social service delivery systems influence the pathways children travel to resilience. In particular, I look at children's navigation to the health resources that are available through service delivery systems and their negotiation with service providers for service once under a provider's mandate. Two case examples are used to illustrate health-enhancing and health-challenging patterns of service provision and utilization among high-risk youth. I then address two questions that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 21 publications
1
59
0
11
Order By: Relevance
“…This fits with Ungar's (2005) findings that youth undergo a dual process of navigating and negotiating resources. It also extends Ungar's (2005) findings by providing suggestions for how service providers could support youth navigating and negotiating social service systems. The participants emphasized the importance of service providers getting to know the youth and their circumstances, spending time "understanding who we are" (Kris).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This fits with Ungar's (2005) findings that youth undergo a dual process of navigating and negotiating resources. It also extends Ungar's (2005) findings by providing suggestions for how service providers could support youth navigating and negotiating social service systems. The participants emphasized the importance of service providers getting to know the youth and their circumstances, spending time "understanding who we are" (Kris).…”
Section: Discussionsupporting
confidence: 88%
“…Ungar (2006) found that these children and youth go through a dual process of navigating and negotiating in order to locate resources and services. There is little research regarding the influence of power, marginalization, or personal agency of the children and youth accessing social services; rather, some have suggested that the main focus has been on intervention and outcomes (Karabanow, 2010;Ungar, 2005). Ungar (2005) argues that researchers need to spend more time engaging with the youth who access these services, and considering how their personal agency influences their ability to access social resources and supports.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Al contrario, las instituciones de la sociedad son llamadas a proveer servicios y oportunidades para los más vulnerables (Ungar 2005). A este tipo de Resiliencia se le llama resiliencia transformativa, definiéndose como la capacidad de una sociedad determinada de cambiar la adversidad y las amenazas en oportunidades de transformación positiva (Valikangas 2010).Desde esta mirada la resiliencia se entiende como un fenómeno contextualizado.…”
Section: Resiliencia Y Las Respuestas Institucionales Ante La Adversidadunclassified
“…Psychological research on educational resilience is still limited and typically focuses on identifying the individual characteristics of resilient students who thrive academically in the face of adversity (Williams & Bryan, 2013). Example characteristics include optimism, intrinsic motivation, assertiveness, the ability to solve problems, perceived social support, and having goals and aspirations (Ungar, 2005). As a result, these and other characteristics are targeted in school-related interventions, but as Williams and Portman (2014) point out-and parallel to the debate among researchers of resilience more generally-viewing resilience as a fixed trait rather than a combination of traits and external protective factors disallows any efforts to strengthen it in the face of risks and traumas.…”
mentioning
confidence: 99%